The preventative effects of Lactococcus Lactis metabolites against LPS-induced sepsis - Fu, Yue; Zhang, Song; Yue, Qiulin; An, Zaiyong; Zhao, Minghan; Zhao, Chen; Sun, Xin; Li, Kunlun; Li, Baojun; Zhao, Lin; Su, Le (Frontiers in Microbiology, 2024)
Introduction Sepsis is a syndrome of organ dysfunction caused by a dysregulated host response to infection and septic shock. Currently, antibiotic therapy is the standard treatment for sepsis, but it can lead to drug resistance. The disturbance of the gut microbiota which is affected by sepsis could lead to the development of organ failure. It is reported that probiotics could shape the gut microbiota, potentially controlling a variety of intestinal diseases and promoting whole-body health. Methods In this study, we evaluated the preventive effects of intra- and extracellular products of probiotics on sepsis. The extracellular products of Lactococcus lactis (L. lactis) were identified through the in vivo cell experiments. The preventive effect and mechanism of L. lactis extracellular products on mouse sepsis were further explored through HE staining, mouse survival rate measurement, chip analysis, etc. Results L. lactis extracellular products increase cell survival and significantly reduce inflammatory factors secreted in a cellular sepsis model. In in vivo experiments in mice, our samples attenuated sepsis-induced pulmonary edema and inflammatory infiltrates in the lungs of mice, and reduced mortality and inflammatory factor levels within the serum of mice. Finally, the mechanism of sepsis prevention by lactic acid bacteria is suggested. Extracellular products of L. lactis could effectively prevent sepsis episodes. Discussion In animal experiments, we reported that extracellular products of L. lactis can effectively prevent sepsis, and preliminarily discussed the pathological mechanism, which provides more ideas for the prevention of sepsis. In the future, probiotics may be considered a new way to prevent sepsis.